The traditio legis : anatomy of an image - Couzin, Robert (Archaeopress archaeology., 2015)
The bearded and mature figure of Christ stands majestically raising his right hand, open palm facing the viewer. In his left he holds an unfurled scroll. Saints Peter and Paul appear on either side, Peter approaching to catch or protect the dangling bookroll. This image, the so-called traditio legis, first appeared in late fourthcentury Rome in a variety of media, from the monumental to the miniature, including mosaic, catacomb painting, gold-glass and, the most numerous group, marble relief carving on sarcophagi. This monograph engages in a close reading of the traditio legis, highlighting its novelty and complexity to early Christian viewers.